MPK3 mediated phosphorylation inhibits the dimerization of ABI5 to fine-tune the ABA signaling in Arabidopsis - Bhagat, Prakash Kumar (Plant physiology and biochemistry : PPB, 2025)
Copyright © 2025 Elsevier Masson SAS. All rights reserved.